Node-link simultaneous mapping based multi-type service resource orchestration algorithm - FENG Chuan; ZHANG Xu; MA Tianchun; GUO Lei (Tongxin xuebao)
To tackle the issues of a high blocking rate of virtual requests and underutilization of physical network resources, a heuristic algorithm for orchestrating multi-type service resources was proposed by simultaneously mapping nodes and links. The physical network node attributes were considered when mapping the first node, the physical network node attributes and link attributes were comprehensively considered when mapping node-link tuples, and the network link attributes were considered when mapping links, so as to find the mapping policy for virtual network requests in the underlying physical network containing multiple types of service resources. Simulation results show that the proposed algorithm can reduce the blocking rate of virtual network requests and improve the utilization efficiency of multiple types of resources in the physical network.